Long-term Fertilization Structures Bacterial and Archaeal Communities along Soil Depth Gradient in a Paddy Soil - Gu, Yunfu; Wang, Yingyan; Lu, Sheng’e; Xiang, Quanju; Yu, Xiumei; Zhao, Ke; Zou, Likou; Chen, Qiang; Tu, Shihua; Zhang, Xiaoping (Frontiers in Microbiology, 2017)
Soil microbes provide important ecosystem services. Though the effects of changes in nutrient availability due to fertilization on the soil microbial communities in the topsoil (tilled layer, 0-20 cm) have been extensively explored, the effects on communities and their associations with soil nutrients in the subsoil (below 20 cm) which is rarely impacted by tillage are still unclear. 16S rRNA gene amplicon sequencing was used to investigate bacterial and archaeal communities in a Pup-Calric-Entisol soil treated for 32 years with chemical fertilizer (CF) and CF combined with farmyard manure (CFM), and to reveal links between soil properties and specific bacterial and archaeal taxa in both the top- and subsoil. The results showed that both CF and CFM treatments increased soil organic carbon (SOC), soil moisture (MO) and total nitrogen (TN) while decreased the nitrate_N content through the profile. Fertilizer applications also increased Olsen phosphorus (OP) content in most soil layers. Microbial communities in the topsoil were significantly different from those in subsoil (p<0.01). Compared to the CF treatment, taxa such as Nitrososphaera, Nitrospira, and several members of Acidobacteria in topsoil and Subdivision3 genera incertae sedis, Leptolinea, and Bellilinea in subsoil were substantially more abundant in CFM. A co-occurrence based network analysis demonstrated that SOC and OP were the most important soil parameters that positively correlated with specific bacterial and archaeal taxa in topsoil and subsoil, respectively. Hydrogenophaga was identified as the keystone genus in the topsoil, while genera Phenylobacterium and Steroidobacter were identified as the keystone taxa in subsoil. The taxa identified above are involved in the decomposition of complex organic compounds and soil carbon, nitrogen, and phosphorus transformations. This study revealed that the spatial variability of soil properties due to long term fertilization strongly shapes the bacterial and archaeal community composition and their interactions at both high and low taxonomic levels across the whole soil profile.